Pengaruh Co-Firing Biomasa Kayu Kaliandra Dan Batu Bara Terhadap Performa Dan Emisi Gas Buang PLTU - Sa’u, Putra Adhitya Frensly; Jasron, Jahirwan Ut; Sanusi, Arifin (TURBO [Tulisan Riset Berbasis Online], 2024)
Fossil fuels such as coal still dominate as fuel for power plants worldwide. Using fossil fuels in most power plants can increase greenhouse gas (GHG) emissions, which affect climate change. Biomass is a renewable energy source expected to reduce greenhouse gas emissions. The use of biomass energy sources as a mixture of fossil fuels, known as co-firing in power plants, has been widely done to reduce dependence on fossil fuels. This research will review the influence of biomass mixture on the efficiency of coal power plant boilers. The mixture's composition and the type of biomass used will significantly affect the Boiler's efficiency. The percentage of biomass composition, as well as the proper combustion settings, will be able to produce optimal boiler efficiency. The study in this research is expected to provide an overview of the performance of a power plant that performs co-firing so that in addition to getting the benefits of reducing greenhouse gas emissions, good boiler efficiency is also obtained.